[OP.2C.07] ARE YOU REALLY AS OLD AS YOUR ARTERIES? PREDICTING BIOLOGICAL AGE USING CARDIO-ANKLE VASCULAR INDEX AS A MARKER OF VASCULAR STIFFNESS. (September 2017) - Kirkham, F.; Mills, C.; Nambier, K.; Timeyin, J.; Davies, K.A.; Kern, F.; Cruickshank, J.K.; Rajkumar, C.
Abstract : Objective: The association between age and vascular parameters has been recognised for centuries, since 17th century physician Thomas Sydenham claimed that "a man is as old as his arteries." Arterial stiffness closely relates to the ageing process but few efforts have been made to predict biological age using vascular compliance. This study investigated the correlation between vascular stiffness and chronological age to assess whether measurements such as cardio-ankle vascular index (CAVI) and pulse wave velocity (PWV) could be used to predict biological age. Design and method: 312 participants (180 men, 132 women), age 63.7 ± 12.9 (mean ± SD), range 25–92 years were enrolled into a study of vascular parameters. The following were measured: CAVI using VaSera VS-1500N ® (Fukuda Denshi, Japan); PWV in the carotid-femoral region (cfPWV) using Complior ® (ALAM Medical, France) and Arteriograph™ (TensioMed, Hungary); brachial blood pressure using OMRON705-IT. Results: The results (mean ± SE) were CAVI = 8.92 ± 0.10, cfPWV = 9.78 ± 0.16 m/sec, brachial systolic blood pressure = 140 ± 1 mmHg. CAVI and cfPWV increased with age (r = 0.63, p < 0.001 and r = 0.37, p < 0.001 respectively). The correlation between age and CAVI was greater in males (r = 0.71, p < 0.001) than females (r = 0.54, p < 0.001) as it was marginally between age and cfPW; males (r = 0.39, p < 0.001) vs females (r = 0.35, p < 0.001). A multivariate regression analysis on the entire population, with age as the dependent factor and average CAVI and cfPWV as independent parameters showed that only CAVI (beta = 0.497, p < 0.001) was significantly associated with age. A multivariate regression analysis performed with average CAVI as the dependent factor and age (standardised Beta = 0.577, p < 0.001), BMI (standardised Beta = −0.205, p < 0.001), systolic BP (standardised Beta = 0.249, p < 0.001) and gender (standardised Beta = −0.208, p < 0.001) as the independent parameters showed that CAVI was significantly associated with all these factors. Conclusions: These results suggest that both CAVI and cfPWV correlate with chronological age, with CAVI more closely related to ageing than cfPWV. Thus, CAVI may be a useful predictor of vascular ageing.